False prophets and preachers : Henry Gresbeck's account of the Anabaptist kingdom of Münster - Gresbeck, Heinrich, active 1540 (Early modern studies series ;, 2016)
"In February 1534, a radical group of Anabaptists, gripped with apocalyptic fervor, seized the city of Münster and established an idealistic communal government that quickly deteriorated into extreme inequality and theocratic totalitarianism. In response, troops hired by the city's prince-bishop laid siege to the city. Fifteen months later, the besieged inhabitants were starving, and, in the dead of the night, five men slipped out. Separated from his fellow escapees, Henry Gresbeck gambled with his life by approaching enemy troops. Taken prisoner, he collaborated with the enemy to devise a plan to recapture Münster and later recorded the only eyewitness account of the Anabaptist kingdom of Münster. Gresbeck's account, which attempts to explain his role in the bizarre events, disappeared into the archives and was largely ignored for centuries. Before now, Gresbeck's account was only available in a heavily edited German copy adapted from inferior manuscripts. Christopher S. Mackay, who previously produced the only modern translation of the main Latin account of these events, has adhered closely to Gresbeck's own words to produce the first complete and accurate English translation of this important primary source"--Publisher's website.